Controllable construction and theoretical simulation of silica aerogel/polymer composites with electrostatic interaction interfaces. (8th September 2021) - Li, Hongyan; Lu, Le; Liu, Hongli; Yuan, Wenjin; Zhang, Bo; Li, Jing; Li, Yajing; Fu, Yongqiang
Abstract: In our previous work, aerogel/polymer composites with electrostatic interaction interface were successfully constructed. Interesting experimental phenomena in heat and stress transfer had also been found. On the basis of these works, we had been thinking about how to control the characteristics of electrostatic interaction phase interface, and how these phase interface characteristics affected the properties of materials. In this paper, the electrostatic interaction phase interface characteristics of the composite were regulated from the aspects of polymer chain movement, charge amount and charge distribution. The effects of phase interface characteristics on stress and heat transfer behavior of the composites were analyzed from the aspects of experimental test characterizations and molecular dynamics simulation. The results showed that the action region of electrostatic attraction phase interface can be controlled by the properties of polymer side chain and charged monomer. The density, heat transfer characteristics and stress transfer behavior of the composites were affected. α-Methyl was beneficial to the thermal stability of the composites, and the thermal conductivity was about 0.012 W m −1 K −1 . When the alkyl side chain was long, the molecular chain arrangement was irregular, the reorientation ability of the molecular chain was poor, and the molecular chain breaks in the compression stage. In the theoretical simulation, it can be found that more charged groups in a single charged part of the molecule led to the increase of cationic density in the organic phase, which made it easier to form effective chemical bonds in the crosslinking process, and the final crosslinking degree was improved. Graphical abstract: Image 1